Development of A Fingerprint Biometric Authentication System For Secure Electronic Voting Machines - Umar, B U; Olaniyi, O M; Ajao, L A; Maliki, D; Okeke, I C (Universitas Muhammadiyah Malang, 2019)
Democratic government in the world today rely on electronic voting as the foremost means of providing credible, transparent and fair elections for the electorate. There is a need for developed electronic voting systems to be security enhanced to ensure the authenticity of the developed system. Traditional paper balloting systems suffer from vote tampering, multiple voting and illegal voting by unregistered voters. They are also, susceptible to under aged voting due to the difficulty in authenticating the identity of prospective voters. Manual collation and publication of vote results also leads to slow response times and inaccuracies in published results. This research paper proposes a system to combat the current challenges through the development of a fingerprint biometric authentication system for secure electronic voting machines. It uses a fingerprint biometric sensor, integrated via Python to verify users of the system. The inclusion of biometrics improves the security features of the system. The secure voting system is built using PHP and easy to use Graphical User Interface was designed using HTML and CSS. Users are required to interact with the machine via a 7” touchscreen interface. From the results, it shows that the developed machine has a minimum response time of 0.6 seconds for specific operation, an FAR of 2%, FRR of 10% and overall system accuracy of 94%. The developed machine is able to combat the challenges of authentication of users, thereby guaranteeing the transparency, credibility, integrity and vote authenticity of the elections.